Level of Knowledge, Washing Hand’s Behavior and Total Number of Bacteria on The Surface Hand Moher At Blawong I, Bantul Regency, Yogyakarta - Dyah Suryani; Wibowo Wibowo (Alliance oh Health Activists (AloHA), 2018)
Background: Practicing the hand washing appropriately and correctly is the easiest and effective way to prevent the outbreak of diseases such as diarrhea, cholera, acute respiratory infections, intestinal worms, influenza, hepatitis A, and even bird flu. Pathogenic germs that may be found in the skin as transient microorganisms are Escherichia coli, Salmonella sp, Shingella sp. Hand is the part of the body which is used daily and always contact with outside. The surface of a toddler's mother's hand is an object that has a high-risk factor of being contaminated with germ numbers. This greatly facilitates contact with food microorganisms in infants. The purpose of this study was to determine the relationship between the level of knowledge and behavior of washing hands with the number of germs on the surface of the hands of toddlers in Blawong I Village, Bantul Regency, Yogyakarta. Method: This study was an observational analytic study with laboratory tests and used a cross-sectional study design. The sample in this study were mothers who have children under five years in Blawong I, Bantul Regency, Yogyakarta. The sample size in the study was 35 mothers. Data analysis used descriptive analysis and bivariate analysis, and an alternative test was used using the Fisher's Exact Test. Results: Knowledge of washing hands showed the p-value 0.059, which means that there was no statistically significant relationship between knowledge and existence of germs in mother’s infants. Hand washing behavior shows the p-value 0.725 which means that there is no statistically significant relationship between behavior and number of germs in mothers of children under five years in Blawong I village, Bantul Regency, Yogyakarta. Conclusion: There was no relationship between knowledge and the incidence of germ in Blawong I Hamlet village, Bantul Regency, Special Region of Yogyakarta. There was no relationship between knowledge and the incidence of germ in Blawong I Village, Bantul Regency, Special Region of Yogyakarta Province. Keywords: knowledge, behavior, hand washing, germ number